LncRNA XIST attenuates hypoxia-induced H9c2 cardiomyocyte injury by targeting the miR-122-5p/FOXP2 axis. (April 2020) - Peng, Hui; Luo, Yuxuan; Ying, Yongjun
Abstract: Objective: To investigate the effect of lncRNA XIST on apoptosis induced by hypoxia. Methods: We analyzed the expression levels of lncRNA XIST and miR-122-5p using RT-qPCR in hypoxia-induced cardiomyocytes. The mechanism by which lncRNA XIST affects myocardial ischemia was investigated using the cell transfection, CCK-8, and dual-luciferase reporter assays, as well as by flowcytometry, western blotting, and RNA immunoprecipitation. Results: Hypoxic H9c2 cells demonstrated a decrease in their migration and invasion abilities and XIST expression and an increase in the extent of their apoptosis and expression of microRNA-122-5p. Overexpression of XIST significantly increased the H9c2 cell viability, enhanced cell migration and invasion, and decreased cell apoptosis in a hypoxic environment. The luciferase activity of XIST-WT in H9c2 cells co-transfected with XIST-WT and microRNA-122-5p mimics had decreased. The results of RNA immunoprecipitation showed that XIST interacted directly with miRNA-122-5p. Overexpression of XIST decreased the level of miRNA-122-5p significantly. mi-122-5p mimics increased H9c2 cell apoptosis and downregulated FOXP2 expression. Overexpression of FOXP2 upregulated the expression of the Bcl-2 protein in H9c2 cells transfected with microRNA-122-5p mimics and inhibited the expression of HIF-alpha, Bax, and the cleaved-caspase 9 protein. Conclusion: lncRNA XIST could regulate the miR-122-5p/FOXP2 axis to attenuate hypoxia-induced H9c2 cardiomyocyte injury. Highlights: Overexpression of XIST increased the H9c2 cell viability, enhanced cell migration and invasion in a hypoxic environment. XIST interacted directly with miRNA-122-5p. Overexpression of XIST decreased miRNA-122-5p. miRNA-122-5p mimics increased H9c2 cell apoptosis and downregulated FOXP2 expression. Overexpression of FOXP2 upregulated Bcl-2 in H9c2 cells transfected with miRNA-122-5p mimics and decreased HIF-alpha, Bax, and the c-caspase 9. lncRNA XIST could regulate the miR-122-5p/FOXP2 axis to attenuate hypoxia-induced H9c2 cardiomyocyte injury.